2008
DOI: 10.1073/pnas.0803341105
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dendritic cell differentiation by HLA-G and ILT4 requires the IL-6—STAT3 signaling pathway

Abstract: The expression of Ig-like transcript (ILT) inhibitory receptors is a characteristic of tolerogenic dendritic cells (DCs). However, the mechanisms of modulation of DCs via ILT receptors remain poorly defined. HLA-G is a preferential ligand for several ILTs. Recently, we demonstrated that triggering of ILT4 by HLA-G1 inhibits maturation of human monocyte-derived conventional DCs and murine DCs from ILT4 transgenic mice, resulting in diminished expression of MHC class II molecules, CD80 and CD86 costimulatory mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(156 citation statements)
references
References 33 publications
9
145
1
1
Order By: Relevance
“…HLA-G was described as a key physiological mediator of maternal-fetal tolerance (38)(39)(40)(41). HLA-G inhibits multiple immune cell functions, including cytolytic functions of uterine and peripheral blood NK cells, Ag-specific cytolytic functions of cytotoxic T lymphocytes, allo-responsiveness of CD4 influence induction of DC tolerance (44). HLA-G-expressing DC-10 and CD4 + T cells accumulate in human deciduas during pregnancy (45).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G was described as a key physiological mediator of maternal-fetal tolerance (38)(39)(40)(41). HLA-G inhibits multiple immune cell functions, including cytolytic functions of uterine and peripheral blood NK cells, Ag-specific cytolytic functions of cytotoxic T lymphocytes, allo-responsiveness of CD4 influence induction of DC tolerance (44). HLA-G-expressing DC-10 and CD4 + T cells accumulate in human deciduas during pregnancy (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was also reported that several factors, such as IL-6, released by solid and liquid tumours affecting the maturation pathway of DCs (Liang et al 2008;Orsini et al 2003;Ratta et al 2002). Pancreatic cancer patient sera containing high levels of IL-6 significantly blocked the maturation of Mo-derived CD14 -CD1a ?…”
Section: Cd34mentioning
confidence: 99%
“…and CD8 ? T cells allostimulatory activity (Liang et al 2008). In addition, a functional defect in DCs from peripheral blood of myeloma and chronic lymphocytic leukaemia patients was partially due to an overproduction of IL-6 (Orsini et al 2003;Ratta et al 2002).…”
Section: Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…LILRB2, but not LILRB1, recognizes HLA-G free heavy chains, 35,36 increasing its inhibitory effects on costimulation and T-cell responses. 37 Ectopic expression of HLA-G itself is sufficient to induce the up-regulation of inhibitory LILR, 38 and expression of both HLA-G and inhibitory LILR is up-regulated through the action of IL-10. 25,26,39,40 Ectopic expression of HLA-G as a high-affinity ligand for inhibitory LILR is likely to be an important factor in determining clinical outcomes in transplant tolerance, infection and cancer.…”
Section: Hla-g As a High-affinity Ligand For Lilrb1 And Lilrb2mentioning
confidence: 99%